Private Ratings, Public Regulations - Kruck, A. author. aut Link
XVI, 205 p.
Keywords: Credit rating agencies play a powerful and contentious role in the governance of global financial markets. Introducing an original framework for delegating political authority to private actors, this book explains common trends in the regulatory use of private ratings for public purposes and analyzes regulatory changes after the Financial Crisis.